Dirasat naqdiyah li zawahir fi al-shi'r al-'Arabi - al-Dukhayli, Husayn'Ali'Abd al-Husayn ('Amman : Dar al-Hamid, 2011)
Arabic poetry; history and criticism; Jamal al-Din, Mustafa, 1927-; criticism and interpretation
Keywords: Jamal al-Din, Mustafa, -- 1927- -- Criticism and interpretation; Arabic poetry -- History and criticism